A SURVEY OF CRYPTOWALLETS AND THEIR SECURITY MECHANISMS (International Journal of Food and Nutritional Sciences, 2022)
A cryptocurrency wallet is simply a wallet for holding cryptocurrency. It can be a device, medium, system or service. In addition to storing the keys, the crypto currency wallet often also provides encryption and / or data signing functionality. Cryptocurrency wallet is an app that allows cryptocurrencies users to store digital assets. It keeps track of the encryption keys used for digitally signing transactions and to store addresses on a blockchain where the specific assets resides. It is very important to secure keys in cryptocurrencies, as they are the only way to prove ownership of digital assets. In this paper, the authentication mechanisms used in the different cryptocurrency wallets are discussed. The findings indicate hardware wallets are most secure cryptowallets. Also, software wallets implementing security mechanism like U2F, passphrase, encryption along with AML compliance and conducting security audits are secure. Software wallets are used with hardware wallets for storing cryptocurrency.